Мовчання в епістолярній поведінці Лесі Українки - Богдан, Світлана; Bohdan, Svitlana (Східноєвропейський національний університет, 2013)
У статті розглянуто особливості мовчання як елемента комунікативної поведінки в епістолярних текстах Лесі Українки. Основну увагу зосереджено на з’ясуванні об’єктивних і суб’єктивних мотивів епістолярного мовчання адресантки, на типових виправдальних і коментувальних контекстах. Проаналізовано реєстр мовних одиниць, що експлікують особистісне мовчання Лесі Українки, а також установлено його диференційні ознаки. The article is devoted to peculiarities of silence as an element of a communicative action in epistolary texts of Lesia Ukrainka. A main attention is concentrated on a clarification of objective and subjective motives in epistolary silence of the addresser and on typical justificative and commentive contexts. It is analysed a glossary among language units which create explicitness to personal silence of Lesia Ukrainka. A main role belongs to such basic lexemes as silence. The article represents differential signs of Lesia Ukrainka’s epistolary silence which is different with its motivation and improvidence and is harmoniously correlated with an attempt to keep a rhythm of epistolary dialogues.
Silence in an Epistolary Action of Lesia Ukrainka
Keywords: мовчання; епістолярна поведінка; мотиви; ритміка епістолярних діалогів; silence; an epistolary action; motives; a rhythm of epistolary dialogues